The INFLUENCE OF FIRM SIZE, BUDGETING POLICY, RISK-BASED CAPITAL (RBC), NET PREMIUM GROWTH, AND FIRM PROFIT ON FIRM VALUE IN THE INSURANCE COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE - sitompul, saleh (Asosiasi Dosen Akuntansi Indonesia, 2018)
The objective of this research was to examine and analyze the influence of firm size, budgeting policy, risk-based capital, net premium growth, and firm profit on the firm value of insurance companies listed on the Indonesia Stock Exchange. The population was all 9 insurance companies listed on the Indonesia Stock Exchange in the period from 2005 until 2016, and all of them were used as the samples. The data were analyzed by using multiple linear regression analysis with an E-views 7 software. The research results demonstrated that firm size, budgeting policy, risk-based capital, net premium growth, and firm profit simultaneously had significant influence on firm value. Partially, only firm size and profit had significant but negative influence on firm value. Budgeting policy, risk-based capital, and net premium growth had insignificant influence on firm value. The determining coefficient was 62.25% which indicated that firm size, budgeting policy, risk-based capital, net premium growth, and firm profit simultaneously had influence of 62.25% on firm value, and the remaining 37.45% was influenced by other factors excluded from the variables in this research.